Governing the Water-Energy-Food Nexus Related to Hydropower on Shared Rivers—The Role of Regional Organizations - Dombrowsky, Ines; Hensengerth, Oliver (Frontiers in Environmental Science, 2018)
An evolving literature on the Water-Energy-Food (WEF) nexus argues that there is a need to better understand the conditions under which nexus coordination may occur. A case in point are hydropower investments on shared rivers which might impact the provision of energy, water and food security across borders. In international basins, governing the WEF nexus impacts of hydropower relies on voluntary negotiations between the respective countries involved. It has been argued that such negotiations may be facilitated by regional organizations, such as international river basin organizations (IRBOs), but this claim has hardly been investigated systematically. Drawing on regime theory in international relations and the literature on benefit sharing, this paper asks what role regional organizations may play in governing hydropower-related WEF nexus impacts. It compares three cases of hydropower planning on shared rivers. The Rusumo Falls and the Ruzizi III hydropower projects (HPPs) are joint investments in Africa’s Great Lakes region facilitated by an IRBO and a regional energy organization respectively. On the Mekong, Laos is constructing the Xayaburi dam despite reservations by the Mekong River Commission and downstream riparians. The paper finds IRBOs and regional energy organizations may play a role in facilitating cross-border nexus governance by supporting benefit-sharing arrangements and by fostering the application of environmental and social safeguards and international law principles. However, it also shows that the influence of regional organizations varies, and how successfully they support nexus governance also depends on whether the HPP is planned unilaterally or jointly; the availability and consensus on data on nexus impacts; and the presence or absence of donors and private sector capital and investors.